1995
DOI: 10.1002/jbm.820290813
|View full text |Cite
|
Sign up to set email alerts
|

Contact activation of the plasma coagulation cascade. I. Procoagulant surface chemistry and energy

Abstract: Contact activation of the intrinsic pathway of porcine blood plasma coagulation is shown to be a steep exponential-like function of procoagulant surface energy, with low activation observed for poorly water-wettable surfaces and very high activation for fully water-wettable surfaces. Test procoagulants studied were a system of oxidized polystyrene films with varying wettability (surface energy) and glass discs bearing close-packed self-assembled silane monolayers (SAMs) with well-defined chemistry consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(169 citation statements)
references
References 19 publications
13
149
2
Order By: Relevance
“…The reduced levels of fibrinogen adsorption that are shown in Figure 7 are significant, implying that the material has a relatively lower affinity to retain fibrinogen, a protein that is dominant in the formation of blood clots 35 and that has been associated with platelet activation on polyurethane surface. 32,36,37 Recently, Vogler et al 38,39 used glass discs bearing 12 kinds of close-packed self-assembled monolayers to investigate the relationship between coagulation and surface wettability. The results showed that the -(CH 2 ) 2 (CF 2 ) 7 CF 3 surface, the least wettable surface among their testing substrates, induced the least plasma coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced levels of fibrinogen adsorption that are shown in Figure 7 are significant, implying that the material has a relatively lower affinity to retain fibrinogen, a protein that is dominant in the formation of blood clots 35 and that has been associated with platelet activation on polyurethane surface. 32,36,37 Recently, Vogler et al 38,39 used glass discs bearing 12 kinds of close-packed self-assembled monolayers to investigate the relationship between coagulation and surface wettability. The results showed that the -(CH 2 ) 2 (CF 2 ) 7 CF 3 surface, the least wettable surface among their testing substrates, induced the least plasma coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Wettability affects protein adsorption, platelet adhesion/activation, blood coagulation and cell and bacterial adhesion [12][13][14][15][16][17]. However, observations regarding the effects of surface wettability on protein adhesion have not always been consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Besides cell culture, the behavior of materials in contact with biological fluid is of tremendous importance for biocompatibility in medicine and pharmacy. It has long been recognized that several negatively charged materials (glass, kaolin, celite, dextran sulfate polymers) induce fast blood clotting [3,4]. The "contact activation pathway" of the plasma coagulation cascade is due to factor XII activation.…”
Section: Importance Of Protein-materials Interactions In Med-mentioning
confidence: 99%